Theophylact, Archbishop of Ohrid – Byzantine shepherd of the Bulgarian „flock” - Leszka, Mirosław J. (Balcanica Posnaniensia. Acta et studia, 2009)
In 1018, Bulgarian lands were incorporated into the Byzantine Empire, which entailed a reorganisation of political and ecclesiastical structures. One of the key elements of this policy was the transformed Ohrid Metropolis, which was granted autocephaly. It was gradually headed by Greek hierarchs, among whom Theophylact of Ohrid stood out – an outstanding rhetorician and intellectual, who came from the circles of the Constantinople elite. He is a controversial figure – he is sometimes portrayed as a tool of Byzantine imperialism and an opponent of the Slavs, and sometimes as a shepherd who, despite his aversion to provincial life, tried to care for the community entrusted to him. The aim of the article is to present Theophylact's complex activities in Ohrid and to analyse his attitude towards the Bulgarians in the light of the surviving sources. The research is based primarily on his extensive correspondence (about 130 letters) and two hagiographic works. The source analysis is supplemented by interpretations from contemporary Byzantine and Bulgarian historiography. The sources paint a picture of a clergyman who was critical of the ‘barbaric’ customs of the Bulgarians, but who also defended them against excessive fiscal oppression and the arbitrariness of imperial officials. Theophylact's hagiographic work testifies to his appreciation of the legacy of St. Clement, St. Naum and the Bulgarian ruler Boris I Michael, whom he presents as a model Christian monarch, almost a saint. Theophylact cannot be clearly defined as an opponent or defender of the Bulgarians. His attitude was full of tension and ambivalence, resulting both from his loyalty to Byzantium and his pastoral concern for the community entrusted to him.